2022
DOI: 10.3389/fimmu.2022.934083
|View full text |Cite
|
Sign up to set email alerts
|

Classification of colon adenocarcinoma based on immunological characterizations: Implications for prognosis and immunotherapy

Abstract: Accurate immune molecular typing is pivotal for screening out patients with colon adenocarcinoma (COAD) who may benefit from immunotherapy and whose tumor microenvironment (TME) was needed for reprogramming to beneficial immune-mediated responses. However, little is known about the immune characteristic of COAD. Here, by calculating the enrichment score of immune characteristics in three online COAD datasets (TCGA-COAD, GSE39582, and GSE17538), we identified 17 prognostic-related immune characteristics that ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Immunotherapy, as one of the most likely therapeutic cures for tumors, is classified into two main categories: immune cell therapy and immune checkpoint therapy, and has been applied in the clinical treatment of a variety of tumors with encouraging therapeutic results [32][33][34][35]. For treating COAD patients, the immune checkpoint-related medications nabolutumab and pablizumab are now being used in clinical trials [36]. Nevertheless, due to a lack of biomarkers and models to predict patient response and prognosis to immunotherapy, low response rates to immunotherapy, and the fact that only some patients indicate treatment, immunotherapy has experienced several challenges in clinical practice [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy, as one of the most likely therapeutic cures for tumors, is classified into two main categories: immune cell therapy and immune checkpoint therapy, and has been applied in the clinical treatment of a variety of tumors with encouraging therapeutic results [32][33][34][35]. For treating COAD patients, the immune checkpoint-related medications nabolutumab and pablizumab are now being used in clinical trials [36]. Nevertheless, due to a lack of biomarkers and models to predict patient response and prognosis to immunotherapy, low response rates to immunotherapy, and the fact that only some patients indicate treatment, immunotherapy has experienced several challenges in clinical practice [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the formation of TLS is mediated by certain pro-inflammatory cytokines and TNF receptor family members, and involves the participation of fibroblasts, perivascular myofibroblasts, and stromal cells (55). However, in gastrointestinal cancer, a large number of patients have low tumor mutation burden and lack immune cell infiltration, making their tumor microenvironment "cold" and resulting in poor response to emerging therapies targeting the tumor immune microenvironment, such as immunotherapy (56,57). Hooren et al discovered the formation of TLS during the process of transforming the solid tumor immune microenvironment from "cold" to "hot" using a CD40 agonist, and TLS was found to be correlated with increased infiltration of T cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…In recent year, algorithms have been developed to predict tumor purity using gene expression data based on the TCGA database. For example, (36,37), breast cancer (38,39), colorectal cancer (40)(41)(42) and hepatocellular carcinoma (43), which demonstrated that such big-data-based algorithms are effective, although its utility on immune and/or stromal scores in glioblastoma multiforme (GBM) has not been explored in detail.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%